Water filter fabrication using activated charcoals / Noor Syaizetty Mohamad Sakdun - Mohamad Sakdun, Noor Syaizetty (2018)
This project will present a basic design and fabrication of activated carbon from agricultural wastes (coconut shells) and other natural sources (gravel stones and sands) for water purification in rural area in Malaysia intended to satisfy the demand of clean water. The activated carbon (AC) contents produced about 80 and 90 volumes percentage of impurities removed, depending on the type of agricultural waste that used in water purification. The absorption and turbidity test were carried out that indicates the activated carbon (AC) with favourable physicochemical properties can be produced locally from agricultural wastes such as corn cobs, coconut shells and many others. Furthermore, this water purification also has higher potential to be implement in our domestic areas especially in rural areas which is important to ensure the quality of water usage in daily life which is free from hazardous material. The results that obtained are then discussed for the uses of activated carbon filter in water purification.